Product Quality, Ambassador Brand and Advertisement on the Decision to Purchase Wardah Facial Cleansing Soap in Ambon City - Erlinda Tehuayo; Merry M. Pelupessy; Faradilla Basalamah (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of product quality, brand ambassadors and advertising on purchasing decisions to purchase Wardah facial cleansing soap in Ambon City. This research is a quantitative descriptive research. the population in this study were consumers of warda facial cleansing soap and the number of samples was 106 respondents. By using a questionnaire as a data collection tool. Sampling using non probability sampling technique with purposive sampling method. The data analysis method used is Multiple Linear Regression. Based on the results of the multiple regression test, it shows that the product quality variable has a positive and significant influence on the purchasing decision variable. Furthermore, the brand ambassador variable has a positive and significant influence on purchasing decisions and the advertising variable has a positive and significant influence on purchasing decisions.